TEACHING MEDICAL CONDITIONS IN NURSING EDUCATION (Лучшие интеллектуальные исследования, 2025)
Abstract: A thorough understanding of medical conditions is essential for nursing students to deliver effective patient care. This article emphasizes the importance of teaching common and critical diseases in nursing education, highlighting their relevance and strategies to integrate them into the curriculum effectively.